Efektivitas Monitoring Retribusi Harian Pasar Di Perusahaan Umum Daerah Pasar Palembang Jaya - Firman, Firman; Sulastri, Sri; Sutinah, Sutinah (@-Publik: Jurnal Administrasi Publik, 2024)
The main problem in monitoring daily payments at Perumda Pasar Palembang Jaya is the lack of effectiveness of supervision, especially in traditional markets, which results in market potential not being fully utilized. This hampers contributions to local original income. In addition, the lack of employee ability to monitor daily levies leads to fraud, limited data collection, low levy rates, as well as inadequate market conditions which harm users. This research aims to determine the effectiveness of monitoring daily market levies at Perumda Pasar Palembang Jaya, especially at Padang Tuesday Market and Soak Bato Market, which is carried out by daily market levy officers. This research is a qualitative descriptive research using data from observation, interviews and documentation. The effectiveness of monitoring daily market levies at Perumda Pasar Palembang Jaya using the theory of Gibson et. al (Makmur, 2008) consists of several dimensions of Productivity, Quality, Efficiency, Flexibility, Satisfaction, Excellence; and Development. The results of the research show that supervision of daily market levy fees is currently not running effectively because supervision of daily levies at Padang Tuesday Market and Soak Bato market is only carried out once a week, resulting in fraud and illegal levies occurring in the collection of daily market levies by not providing tickets as proof of payment of levies. daily market fees to traders in accordance with predetermined rates, and the ability of daily market levy management officers is still limited in supervising the running of the daily Padang Tuesday market and Soak Bato market levies, resulting in the Padang Tuesday market and Soak Bato market not being managed properly. market levies.